Current Situation of Acute Rheumatic Fever and Rheumatic Heart Disease in Latin America and the Caribbean: A Systematic Review - Maria Alejandra Jaimes-Reyes; Manuel Urina-Jassir; Manuel Urina-Triana; Miguel Urina-Triana (Ubiquity Press, 2022)
Background: Rheumatic heart disease (RHD) disproportionately affects low-income and middle-income countries. Latin America and the Caribbean (LAC) have been less represented in scientific literature. We aimed to describe the epidemiology, burden and implemented screening and prevention strategies of RHD in LAC. Methods: We systematically searched PubMed, Embase, LILACS, and SciELO from 1990 to April 2021. Observational and experimental studies that described data on the epidemiology, burden, or prevention/screening strategies of RHD, regardless of age or language, were included. The risk of bias was assessed by previously published tools depending on their study design. Pre-specified data were independently extracted and presented by each topic (epidemiology, burden, prevention/screening). PROSPERO registration number: CRD42021250043. Results: Forty-eight studies out of 1692 non-duplicate records met the eligibility criteria. They were mainly from Brazil, observational in design, and hospital-based. Data on the epidemiology of acute rheumatic fever (ARF) was not recent (most before 2000) with studies describing decreasing incidence through the years. The prevalence of RHD was described in six studies, ranging from 0.24 to 48 per 1,000 among studies evaluating schoolchildren. Nine studies described data based on admissions, ranging from 0.04% to 7.1% in single-center studies. Twenty-four studies assessed the burden of RHD with most of them reporting mortality rates/proportions and complications such as the need for intervention, atrial fibrillation, or embolism. Six preventive strategies were identified that included educational, register-based, and/or secondary prophylaxis strategies. Three well-established echocardiographic screening studies in Brazil and Peru were identified. Conclusions: Most ARF/RHD research in LAC comes from a single country, Brazil where preventive/screening efforts have been conducted. There was a paucity of data from several countries in the region, reflecting the need for epidemiological studies from more countries in LAC which will provide a better picture of the current situation of ARF/RHD and guide the implementation of preventive strategies.